Tomato and Lycopene Feeding Impact Expression of Lipid and Cholesterol Metabolism Genes in Early TRAMP Mouse Model Prostate Carcinogenesis (OR05-05-19). (13th June 2019) - Moran, Nancy; Thomas-Ahner, Jennifer M; Tan, Hsueh-Li; Silva, Ceasar; Hason, Noor; Smith, Josh; Erdman, John; Clinton, Steven
Abstract: Objectives: Epidemiologic evidence suggests consuming tomato and lycopene are associated with a reduced risk of advanced and lethal prostate cancer. Prior studies of prostate cancer prevention in the TRAMP mouse model indicate that lifelong tomato- or lycopene-feeding reduce incidence of early carcinoma by up to 70%, and this effect is dependent on the expression of Bco2 (beta-carotene oxygenase 2, a carotenoid metabolic enzyme). We hypothesize that gene expression patterns will reveal the mechanisms by which these diets act to disrupt early carcinogenesis. Methods: To define the early transcriptional responses in the dorsolateral mouse prostate, TRAMP and wild-type littermate mice were crossed with Bco2+/+  or Bco2−/− mice (C57/Bl6 background). All 4 crosses were fed either control, lycopene, or 10% tomato powder diets from weaning at 3 weeks until 8 weeks. Expression of 84 genes was measured by a prostate cancer-focused PCR array ( n  = 5/group). Protein expression was measured by Western blotting ( n  = 4/group) and serum carotenoids by HPLC ( n  = 3–4/group). Statistical effects of TRAMP and Bco2 genotypes and diet treatment on final body mass ( n  = 6/group), serum lycopene, and gene expression were analyzed by ANOVA (alpha = 0.05). Results: Body masses were not influenced by genotypes or diets. Serum lycopene concentrations were subject to a Bco2 genotype effect ( P  = 0.004), with greater lycopene being present in Bco2 −/− mice than Bco2 +/+ mice, but did not differ by TRAMP genotype nor between lycopene vs tomato diets. The TRAMP genotype influenced the expression of 49 genes, diet impacted expression of 11 genes, and Bco2 genotype influenced expression of 2 genes. Expression of 4 genes, Apc, Mto1, Nfkb1, and Rbm39, were subject to a significant Bco2 x diet interaction . Expression of 5 genes related to lipid metabolism, Fasn, Acaca, Srebf1, Hmgcr, and Ptgs1, were impacted by a diet effect. Conclusions: Semi-targeted analyses suggest tomato and lycopene may affect lipid metabolism in early carcinogenesis. Future studies may elaborate upon specific pathways modulated by tomato and lycopene in early prostate carcinogenesis. Funding Sources: NIH/National Cancer Institute, NIH/National Center for Complementary and Integrative Health, USDA/Agricultural Research Service.